2004
DOI: 10.1016/s0022-5223(04)01143-2
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent mitral regurgitation after annuloplasty for functional ischemic mitral regurgitation

Abstract: Although initial mitral valve replacement would eliminate the risk of postoperative mitral regurgitation, this strategy has been associated with reduced survival. Therefore the development of additional techniques is necessary to achieve more secure repair of functional ischemic mitral regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
116
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(128 citation statements)
references
References 14 publications
9
116
2
1
Order By: Relevance
“…[7][8][9][10] This trend is explained by promising results after MitraClip ® treatment and suboptimal results and increased mortality rates in patients with secondary MR after surgical mitral valve repair. 7,[11][12][13][14][15] For the first time, the COAPT (Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients With Functional Mitral Regurgitation) trial has recently shown a significantly improved survival and a lower rate of hospitalization at 2-years FU in patients with heart failure and severe secondary mitral regurgitation additionally treated by MitraClip ® implantation compared to patients treated by guideline-directed medication, only. 16 However, the…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] This trend is explained by promising results after MitraClip ® treatment and suboptimal results and increased mortality rates in patients with secondary MR after surgical mitral valve repair. 7,[11][12][13][14][15] For the first time, the COAPT (Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients With Functional Mitral Regurgitation) trial has recently shown a significantly improved survival and a lower rate of hospitalization at 2-years FU in patients with heart failure and severe secondary mitral regurgitation additionally treated by MitraClip ® implantation compared to patients treated by guideline-directed medication, only. 16 However, the…”
Section: Introductionmentioning
confidence: 99%
“…In patients with IMR, surgical mitral valve (MV) repair results in a high incidence of recurrent mitral regurgitation (MR) and is associated with poor long-term survival. [10][11][12] This may be attributable in part to the poor understanding of annular geometrical alterations in patients with IMR. There are few investigations that report annular geometrical alterations in IMR in the clinical settings, while most investigations into the pathogenesis of IMR have mainly focused on alterations in ventricular or valvular geometry.…”
mentioning
confidence: 99%
“…[6][7][8][9] Mitral valve repair with an annuloplasty ring has been proven to reduce MR and be a preferred surgery to mitral valve replacement to improve survival rate of patients with coronary artery disease. 10,11 However, approximately 30% of mitral valve repairs result in significant recurrent MR postoperatively, 12,13 and the factors contributing to the return of MR are currently incompletely characterized.…”
mentioning
confidence: 99%
“…A prevailing theory on the return of MR is that adverse left ventricular remodeling following annuloplasty causes papillary muscle displacement, thus leading to recurrent MR. [14][15][16][17][18] In concordance with this theory, relatively few patients experience severe recurrent MR immediately postoperatively, but over the first 6 months following annuloplasty, presumably as the left ventricle undergoes adverse remodeling, significant MR develops in a subset of patients. 13 Thus, this study examined patients whose mitral valve repairs were successful in eliminating MR for at least 6 months, but then MR returned in significant amounts late after the operation.…”
mentioning
confidence: 99%